A novel arthroscopic pre-curved cannula with both flexibility and high stiffness - Park, Chulmin; Kim, Jeongryul; Yonghwan, Moon; Kim, Keri (WILEY, 2022)
Background Curved surgical instruments are being developed to expand the workspace of straight surgical instruments. They are required to have a small diameter and high stiffness. Methods We developed a double-spring pre-curved cannula (DSPC) for electrocauterization, which has curved movements controlled solely by translational motion, and high stiffness via wire tension. It comprises a straight extension spring, pre-curved flat spring and braided high-modulus polyethylene line. A handheld device was designed for intuitive DSPC manipulation. The cannula has a 3.9 mm diameter and serves as a protective tube such that the electrode can safely reach the lesion. Results Experimental results demonstrate that the DSPC has ideal curvature and maximum stiffness of 1.38 N/mm. In a cadaveric study, the DSPC reached the inferior glenohumeral ligament, which conventional surgical instruments cannot access, and surgeons successfully performed electrocauterization. Conclusions The designed DSPC is effective for future use in forceps, curettes and surgical robots.